Cytocompatibility, Antimicrobial and Antioxidant Activity of a Mucoadhesive Biopolymeric Hydrogel Embedding Selenium Nanoparticles Phytosynthesized by Sea Buckthorn Leaf Extract - Naomi Tritean; Luminița Dimitriu; Ștefan-Ovidiu Dima; Rusăndica Stoica; Bogdan Trică; Marius Ghiurea; Ionuț Moraru; Anisoara Cimpean; Florin Oancea; Diana Constantinescu-Aruxandei (MDPI AG, 2023)
Phytosynthesized selenium nanoparticles (SeNPs) are less toxic than the inorganic salts of selenium and show high antioxidant and antibacterial activity. Chitosan prevents microbial biofilm formation and can also determine microbial biofilm dispersal. Never-dried bacterial nanocellulose (NDBNC) is an efficient carrier of bioactive compounds and a flexible nanofibrillar hydrophilic biopolymer. This study aimed to develop a selenium-enriched hydrogel nanoformulation (Se-HNF) based on NDBNC from kombucha fermentation and fungal chitosan with embedded biogenic SeNPs phytosynthesized by an aqueous extract of sea buckthorn leaves (SbLEx)-SeNPsSb-in order to both disperse gingival dysbiotic biofilm and prevent its development. We determined the total phenolic content and antioxidant activity of SbLEx. Liquid chromatography-mass spectrometry (LC-MS) and high-performance liquid chromatography (HPLC) were used for the identification of polyphenols from SbLEx. SeNPsSb were characterized by transmission electron microscopy-energy-dispersive X-ray spectroscopy (TEM-EDX), dynamic light scattering (DLS), zeta potential, Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) in small- and wide-angle X-ray scattering (SAXS and WAXS). The hydrogel nanoformulation with embedded SeNPsSb was characterized by SEM, FTIR, XRD, rheology, mucin binding efficiency, contact angle and interfacial tension measurements. We also assessed the in vitro biocompatibility, antioxidant activity and antimicrobial and antibiofilm potential of SeNPsSb and Se-HNF. TEM, DLS and SAXS evidenced polydisperse SeNPsSb, whereas FTIR highlighted a heterogeneous biocorona with various biocompounds. The contact angle on the polar surface was smaller (52.82 ± 1.23°) than that obtained on the non-polar surface (73.85 ± 0.39°). The interfacial tension was 97.6 ± 0.47 mN/m. The mucin binding efficiency of Se-HNF decreased as the amount of hydrogel decreased, and the SEM analysis showed a relatively compact structure upon mucin contact. FTIR and XRD analyses of Se-HNF evidenced an interaction between BNC and CS through characteristic peak shifting, and the rheological measurements highlighted a pseudoplastic behavior, 0.186 N adhesion force and 0.386 adhesion energy. The results showed a high degree of cytocompatibility and the significant antioxidant and antimicrobial efficiency of SeNPsSb and Se-HNF.